2018
DOI: 10.12911/22998993/86156
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities for the Use of Wood Ashes in Agriculture

Abstract: The aim of the study was to determine the agricultural usefulness of the ashes obtained following the combustion of wood of fourteen tree species (pear tree, apple tree, aspen, ash, alder, birch, poplar, hornbeam, pine, common walnut, oak, hazel, bird cherry and spruce) in home fireplaces. The following physical properties of the ashes were determined: colour, solubility, porosity, absorbability, compression strength, degree of fineness, moisture content and spreadability. In the ashes obtained from the combus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
2
21
0
Order By: Relevance
“…Jakubus and Tatuśko (2016) analysed ashes from combustion of wood and found Mn content of 1088 ppm. Symanowicz et al (2018) determined Mn content in birch ashes at the level of 919.2 mg/kg, in beech at 840.2 mg/kg, alder at 421.5 mg/kg, and spruce at 945.7 mg/ kg.…”
Section: Basic Biomass Components and Calorific Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Jakubus and Tatuśko (2016) analysed ashes from combustion of wood and found Mn content of 1088 ppm. Symanowicz et al (2018) determined Mn content in birch ashes at the level of 919.2 mg/kg, in beech at 840.2 mg/kg, alder at 421.5 mg/kg, and spruce at 945.7 mg/ kg.…”
Section: Basic Biomass Components and Calorific Valuementioning
confidence: 99%
“…According to Kajda-Szcześniak (2014), the highest Ni content was found in ash from the combustion of beech (187.2 mg/kg) and pine (36.98 mg/kg). According to Symanowicz et al (2018), Ni in ash from wood combustion ranges from 32.8 mg/kg (oak) to 91.3 mg/kg (birch). Data from subject literature are characterised by high variability of potentially toxic elements in wood biomass ash (Table 5).…”
Section: Potentially Toxic Elements In Wood Biomass and Ashes From Its Combustionmentioning
confidence: 99%
“…In addition to increasing soil water retention, wood ash provided nutrients to Paiaguás grass, such as Ca, Mg, K and P, necessary for plant development. Symanowicz et al (2018), analyzed ashes and observed good physical and chemical properties and confirmed that they are a source of the macronutrients Ca, C, K, Mg, P, S and N for plants, being suitable for agricultural soils. Similarly, Bezerra et al (2016) investigated the effect of application of wood ash on growth of U. brizantha cv.…”
Section: Effect Of Wood Ash and Soil Water On Plant Heightmentioning
confidence: 67%
“…BRS Paiaguás presents as an alternative for pasture diversification in tropical regions, mainly during the dry season, as it has a high yield of leaves with good nutritive value, resulting in higher weight gains per animal per area (Valle et al, 2013;Euclides et al, 2016). Wood ash has been shown to neutralize soil acidity and provide nutrients such as calcium, magnesium, potassium, phosphorus and micronutrients, which are essential for plant growth and development (Chen et al, 2015;Symanowicz et al, 2018). Most of the bioenergy produced in the world is derived from plant biomass (Souza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of wood as the main construction material is not possible for all types of structural solutions. It has statics-related and technological limitations depending on the limit conditions of its use [41]. The main barrier to more extensive use of wood in construction in Slovakia is a certain degree of prejudice and poor awareness of wood constructions among investors and constructors [42,43].…”
Section: Introductionmentioning
confidence: 99%